Job Creation Law: A New Perspective for Business Actualization of Business Competition and Its Link to Corruption - Jonathan Andreas Sitorus; Handoyo Prasetyo (Dinasti Research, 2024)
This research aims to find out how the criminal law on business competition applies after Law Number 6 of 2023 and find out how the actualization of business actors in unfair business competition is related to the potential for Corruption Crimes. This research uses a normative juridical method through a statutory approach and a conceptual approach. The results of this research are that Law Number 6 of 2023 eliminates the criminal threat of business competition in Law Number 5 of 1999, where this effort is limited to decriminalization without anything else behind it. Then, it was also found that the elimination of the criminal threat of business competition in Law Number 6 of 2023 does not necessarily eliminate the criminal threat of business competition behavior absolutely, it is still possible that there is a threat of criminal acts of corruption which is indicated by unfair business competition. This needs to get the attention of business actors, so in this case the importance of considering the principles of business judgment rules in determining business policies is emphasized in order to avoid this threat.